An atomic ordering based AlInP unicompositional quantum well grown by MOVPE - Tang, Xiaohong (2013)
An AlInP unicompositional single quantum well (QW) structure has been grown and studied by using metal-organic vapor phase epitaxy (MOVPE). The energy bandgap offset of the quantum well is achieved by taking the advantage of the AlInP epilayer’s bandgap energy reduction induced by its CuPt–B type spontaneous atomic ordering instead of by changing the QW layers’ compositions during the MOVPE growth. The degree of the CuPt–B atomic ordering of the AlInP epilayers of the QW structure was controlled by adjusting the input V/III flux ratio during the MOVPE growth. Low temperature photoluminescence (PL) measurement shows strong quantum confinement effect of the grown AlInP unicompositional QWs. After annealing at 900 °C for 30 s, the peak emission wavelength of the QW was measured. It remained at the same wavelength as that of the AlInP barrier layer, which showed the disappearance of the quantum confinement effect of the QW structure. This is attributed to the elimination of the CuPt–B atomic ordering of the AlInP epilayers of the QW sample under a high temperature annealing. The QW structure became a thick disordered AlInP bulky layer after the thermal annealing.